Team collaboration during the concept and viability stage of the development process - Veldsman, Dewald (My University, 2018)
The purpose of the research is to study team collaboration during the concept and viability stage of the property development process. Most construction project teams comprise participants from different professions that combine to form temporary organisations aimed at achieving the common objective of delivering a project. Available tools can facilitate an environment, conducive to better collaboration and integration of people and processes, which ultimately contributes to better value for the producer. However, the implementation of these tools among the professional team in the Johannesburg context is not well understood.
A dissertation submitted in fulfilment of the requirements for the degree of Masters in Science in the School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2018
Keywords: Teams in the workplace; Employee motivation